2020
DOI: 10.14309/ctg.0000000000000262
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Ultrasound Model Based on the Left Gastric Vein in B-Viral Cirrhosis: Noninvasive Prediction of Esophageal Varices

Abstract: OBJECTIVES: To establish and verify a simple noninvasive model based on the left gastric vein (LGV) to predict the grade of esophageal varices (EV) and high-risk EV (HEV), to facilitate clinical follow-up and timely treatment. METHODS: We enrolled 320 patients with B-viral cirrhosis. All patients underwent endoscopy, laboratory tests, liver and spleen stiffness (SS), and ultrasonography. HEV were analyzed using the χ 2 test/ t … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Xu X et al reported that the AUROC of LSPI for diagnosis of small EVs was 0.897 in the training set, whereas the AUROC increased to 0.999 in the validation set [94 ▪ ].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 99%
“…Xu X et al reported that the AUROC of LSPI for diagnosis of small EVs was 0.897 in the training set, whereas the AUROC increased to 0.999 in the validation set [94 ▪ ].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 99%
“…These parameters include presence of ascites, platelet count, prothrombin time, splenic diameter, portal vein diameter, platelet count to spleen diameter ratio, serum albumin and serum bilirubin. 8 Several studies have observed that these non-invasive parameters are strong predictors of esophageal varices. 8,9,10 Several studies have also been done in Pakistan that have used these non-invasive parameters but most of them have analysed each parameter separately and only a few have used various combined scores to predict esophageal varices.…”
Section: Introductionmentioning
confidence: 99%
“…8 Several studies have observed that these non-invasive parameters are strong predictors of esophageal varices. 8,9,10 Several studies have also been done in Pakistan that have used these non-invasive parameters but most of them have analysed each parameter separately and only a few have used various combined scores to predict esophageal varices. 11,12,13 In a developing country like Pakistan endoscopy facilities are limited, expensive, and the endoscopic workload is high.…”
Section: Introductionmentioning
confidence: 99%
“…Several NITs have been developed to rule out VNT, including platelet/MELD strategy 7 , the platelet-albumin criteria 8 , the LGV diameter-SS to PLT ratio index (LSPI) 9 , Platelet count/spleen diameter ratio (PSR) 10 , liver stiffness measurement (LSM) 11 , 12 , spleen stiffness measurement (SSM) 13 , 14 , the Baveno VI criteria (B6C) 15 , the expanded Baveno VI criteria (EB6C) 16 , LSM-spleen diameter (SD) to platelet ratio score (LSPS) 17 , and the VariScreen algorithm 18 , etc. Transient elastography (TE) has been proven to be an accurate and noninvasive technique for assessing hepatic fibrosis and liver cirrhosis 19 .…”
Section: Introductionmentioning
confidence: 99%